2017
DOI: 10.1080/20518196.2016.1252129
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing cultural heritage: public participation and conflict legacy in Finland

Abstract: Following a recent worldwide boom in the democratization of knowledge, crowdsourcing and Participatory GIS, heritage practice increasingly draws on crowdsourced geographical data. In this paper, I discuss a public crowdsourcing of twentieth century conflict heritage in Finland, launched by state-owned broadcasting company Yleisradio. Here emphasis is on analysing the user behaviour and incentives, which can inform analogous future initiatives. Many of the public entries mirror local perspectives on conflict he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…This corroborates our wider research concerning the motivation for the engagement of history enthusiasts and collectors with the WWII material heritage in Finnish Lapland: most of the history hobbyists seem to have personal and local connections to this particular heritage (e.g. Herva et al 2016;Seitsonen 2017). Special interests included professional and scientific expertise.…”
Section: Doing Archaeology With Volunteerssupporting
confidence: 85%
“…This corroborates our wider research concerning the motivation for the engagement of history enthusiasts and collectors with the WWII material heritage in Finnish Lapland: most of the history hobbyists seem to have personal and local connections to this particular heritage (e.g. Herva et al 2016;Seitsonen 2017). Special interests included professional and scientific expertise.…”
Section: Doing Archaeology With Volunteerssupporting
confidence: 85%
“…Contributing to projects aimed at investigating and solving social problems can be a personally empowering experience, as Williams (2013) points out in an article reviewing the different ways in which crowdsourcing is now being applied to contemporary criminal investigation and law enforcement. Participation in heritage projects may likewise help citizens confront and better understand troubling and violent aspects of the past, as well as assisting scholars to better comprehend public perspectives of such subjects (Seitsonen, 2017). Equally, it has been suggested that crowdsourcing helps build a sense of community by 'democratizing history' (Grove, 2011: 6).…”
Section: Discussionmentioning
confidence: 99%
“…Crowdsourcing and citizen scientists are used to great effect in other scientific research, and has been especially popular within the galleries, libraries, archives and museums (known shorthand as GLAM) community (Ridge, 2014). It has also been put to good use in the monitoring of wildlife such as birds (Sullivan et al, 2014), and by media agencies for collecting public knowledge of historical periods such as the First and Second World Wars and the Finnish Civil War (Seitsonen, 2017), to name a few examples.…”
Section: Collecting Heritage Crime Datamentioning
confidence: 99%